Morocco, a New Era of Robotic Surgery - Jihad El anzaoui; Mohammed Mrabti; Abdessamad Elbahri; Mohamed Alami; Ahmed Ameur (Société Internationale d’Urologie Journal)
Robotic surgery has been widely adopted over the past two decades, because it offers significant advantages such as minimally invasive access, precision, ergonomic design, and enhanced safety [...]